2005
DOI: 10.1158/1535-7163.mct-05-0168
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human tumor cell growth in vivo by an orally bioavailable inhibitor of CDC25 phosphatases

Abstract: Cell cycle regulators, such as the CDC25 phosphatases, are potential targets for the development of new anticancer drugs. Here we report the identification and the characterization of BN82685, a quinone-based CDC25 inhibitor that is active in vitro and in vivo. BN82685 inhibits recombinant CDC25A, B, and C phosphatases in vitro. It inhibits the growth of human tumor cell lines with an IC 50 in the submicromolar range, independently of their resistance to chemotherapeutic agents. This inhibitory effect is irrev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 29 publications
(26 reference statements)
1
44
0
Order By: Relevance
“…Initial results support the view that CDC25 is an interesting and important anticancer target, 12,13,23 and considerable effort is currently directed to the identification additional candidate drugs. Here, we describe a novel small molecule bearing two quinone moieties that is a potent inhibitor of CDC25 family members and which inhibits human tumor cell proliferation in both in vitro and in vivo models.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Initial results support the view that CDC25 is an interesting and important anticancer target, 12,13,23 and considerable effort is currently directed to the identification additional candidate drugs. Here, we describe a novel small molecule bearing two quinone moieties that is a potent inhibitor of CDC25 family members and which inhibits human tumor cell proliferation in both in vitro and in vivo models.…”
mentioning
confidence: 69%
“…IRC-083065 was initially coded as BN82685. 13 IRC-083864 is a dry powder freshly prepared in 30% HPB-cyclodextrin vehicle for intravenous dosing and in D5W for oral dosing. Paclitaxel (Natural Pharmaceuticals, Lot No.…”
Section: Preparation Of Irc-083864mentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to further investigate the mechanism by which leukemia cell lines are able to recover from the DNA-damage cell cycle checkpoint in G2, we performed similar experiments to that described in Figure 1a in the presence of the BN82685 compound, a previously described selective chemical inhibitor of CDC25 phosphatases (Brezak et al, 2005). We found that treatment with VP-16 and BN82685 led to a significant decrease in the percentage of mitotic cells over time in the U937 and KG1a cultures and that this occurred in a BN82685 dose-dependent manner (Figures 2a and b), indicating that mitotic entry was impaired following the inhibition of all CDC25 phosphatases.…”
Section: Cdc25b Plays a Role In G2/m Checkpoint Recoverymentioning
confidence: 99%
“…Then, the reaction mixture was diluted to a final concentration of 0.1 μM at which the inhibitors are inactive (data not shown). If the inhibitory effects persist after dilution, the mechanism of action should be considered as irreversible (21). As indicated in Fig.…”
Section: Resultsmentioning
confidence: 99%